KAJIAN ARSITEKTUR LUMBUNG PADI, LOLO GEDANG, KERINCI - Lubis, Romario (Multikultura, 2026)
Rice barns are agrarian vernacular architecture that reflects local knowledge, environmental adaptation, and the socio-cultural values of the supporting community. This study aims to examine the architectural characteristics of traditional rice barns in Lolo Gedang Village, Kerinci, through analysis of form, construction techniques, and cultural context. The method used is descriptive qualitative with inductive reasoning based on literature studies and analysis of the architectural elements of the barn as a cultural artifact. The results show that the Lolo Gedang rice barn is designed adaptively to highland climate conditions, especially in maintaining the quality of grain from humidity and pests, through a stilt system, the use of local wood materials, and a steep roof shape. In addition to its technical function, the rice barn also has social and symbolic meanings related to the customary system and food security of the Kerinci community. This study confirms that the rice barn does not only function as a storage building, but also as a representation of traditional agrarian architecture and culture.